Ca2+-induced whey protein emulgels for the encapsulation of crystalline nobiletin: Effect of nobiletin crystals on the viscoelasticity. (September 2019) - Hu, Yan; Shu, Qiao; Liu, Fei; Lei, Lingling; Li, Bin; Cao, Yanping; Li, Yan
Abstract: Due to the high crystallization, nobiletin was encapsulated by Ca 2+ -induced whey protein concentrate (WPC)-stabilized emulgels. Hydroxypropyl methylcellulose (HPMC) was used to regulate the interfacial properties of emulsions and viscoelasticity of emulgels. The formation of nobiletin crystals were monitored in emulgels and after digestion. Micro-rheometer was used to characterize the viscoelasticity of emulgels. Bioaccessibility of nobiletin was determined by an in vitro digestion model. Ca 2+ crosslinking increased the particle size of WPC-stabilized emulsion, while HPMC/WPC-stabilized emulsions kept smaller particle size. WPC-stabilized emulgels were more apt to syneresis, which could be prevented in the presence of HPMC. Nobiletin crystallization process in emulgels was delayed by HPMC. In the gelation process, HPMC addition increased the viscosity, but decreased the elasticity of emulgels. HPMC interrupted the crosslinking process of WPC and Ca 2+ . After destruction, emulgels had lower viscosity and elasticity, which became lower in the presence of HPMC. The fluctuation of mean square displacement profiles could indicate the formation of nobiletin crystals, which reduced the viscosity and elasticity of emulgels. HPMC increased the bioaccessibility of nobiletin. Higher Ca 2+ concentration was undesirable to enhance the nobiletin bioaccessibility, depending on the structure of emulgels. Graphical abstract: Hydroxypropyl methylcellulose addition as the second emulsifier made the WPC-stabilized emulgels more homogenous and more stable against sysneresis. The formation of nobiletin crystals destructed the structure of emulgels, leading to lower viscosity and elasticity.Image 1020 Highlights: Ca 2+ -induced whey protein-stabilized emulgels were used to encapsulate nobiletin. Hydroxypropyl methylcellulose modulated the viscoelasticity of emulgels. Nobiletin crystals were embedded in the gel network. Formation of nobiletin crystals affected the viscoelasticity of emulgels. Hydroxypropyl methylcellulose addition enhanced the bioaccessibility of nobiletin.